Practical guidance on heart failure diagnosis and management in primary care: recent EPCCS recommendations. - Taylor, CJ; Rutten, FH; Brouwer, JR; Hobbs, FR (Royal College of General Practitioners, 2017)
Heart failure (HF) is a common and costly clinical syndrome, associated with significant morbidity and reduced life expectancy, affecting around 1–2% of adults in developed countries.1 Timely diagnosis is important to optimise evidence-based treatment opportunities, which delay mortality and improve symptoms, but the early stages of HF can be difficult to identify clinically. Primary care has a vital role in providing holistic, person-centred care from first symptoms to end of life. This article summarises the key aspects of HF management for general practice including new areas of diagnostics and drug therapy.